Career Commitment: A Mediating Link Between Emotional intelligence and Career Success - Sultana, Razia; Aldehayyat, Jehad (International Journal of Engineering and Technology, 2018)
This research aspired to investigate the relationship between emotional intelligence (EI), objective career success (OCS) and subjective career success (SCS). In addition, it probes the mediating effect of career commitment (CC) on EI-OCS and EI-SCS relationship. 200 faculty members from five major Pakistani universities were surveyed by means of a close-ended questionnaire. Data were analysed by running CFA and structural equation modelling (SEM). The study results showed a positive relationship between EI-OCS and EI-SCS. However, the relationship was stronger with OCS than SCS. Contrary to our expectations, CC did not fully mediate the relationship; however, partial mediation was found. Study results will facilitate HR practitioners to acknowledge EI as integral factor in employee’s career success. This research extends career success literature by studying EI as one of the pivotal career success predictors. In addition, as a mediator of career success, CC has been given little attention so far and can be considered a key contribution to this study.